Non-Conducive Classroom Environments and Students’ Learning-Related Traumatic Responses: A Qualitative Study among Grade VIII Students - Sofiya Barus; Suzette Hating; Sifra Manalu; Asta Sembiring; Yannece Sihombing; Maria Sihotang (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
A classroom environment is not only a physical space for instruction but also a psychological and social setting that shapes students’ learning experiences. When the classroom is noisy, crowded, poorly ventilated, emotionally unsafe, or marked by negative teacher and peer interaction, students may experience anxiety, avoidance, low motivation, and learning-related traumatic responses. This study aims to analyze how a non-conducive classroom environment contributes to students’ learning-related traumatic responses among Grade VIII students. This study employed a descriptive qualitative design. Data were collected through classroom observation, in-depth interview, and field notes. The findings show that students perceived the classroom as non-conducive when it was noisy, physically uncomfortable, poorly ventilated, poorly organized, and insufficiently managed by the teacher. Students also reported emotional pressure caused by authoritarian teacher behavior, repeated peer ridicule, lack of emotional support, and limited student voice in classroom decision-making. These conditions were associated with fear of participation, reluctance to ask questions, anxiety before certain lessons, physical complaints such as headache or stomach discomfort, withdrawal from peer interaction, declining motivation, and reduced academic engagement. The study concludes that learning-related traumatic responses are shaped by the interaction of physical, social, and emotional classroom factors. Therefore, schools should develop safer, more supportive, and trauma-informed classroom environments through positive teacher-student relationships, anti-bullying prevention, better classroom management, student counseling, and improvement of physical classroom conditions.